ANALISIS PENERAPAN AGEN46 SEBAGAI PENYEDIA LAYANAN KEUANGAN TANPA KANTOR (BRANCHLESS BANKING) DAN UPAYA PENDORONG FINANCIAL INCLUSION - Ghonimah Zumroatun Ainiyah; Fadilah Nurkholik; Eling Ri Kurniati (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2021)
ABSTRACT The development of the financial sector, especially the banking sector, can increase banking access to the public. The problem that occurred before the implementation of Agen46 was that it was difficult for people to get financial services, especially in rural communities. There are still many people who do not know, use, and get financial services, which is a complex problem. The number of Agen46 in Banjarnegara Regency is 160, while the population in Banjarnegara is 923,192 people. The comparison between the number of Agen46 and the number of residents has not met the needs of the community. Branchless banking /smart behavior, encourages banking institutions to develop financial service innovations to encourage financial inclusion. PT Bank Negara Indonesia (Persero), Tbk develops financial service innovations through Agen46. The purpose of this study was to determine the role of Agen46 in its application as a financial service without offices to meet the financial needs of the community. This research is a type of research using a qualitative approach. The data used in this study are primary data by conducting interviews and observations at Agen46 in the Banjarnegara Regency in accordance with the research criteria. The sampling technique used in this study was purposive sampling technique, where the sampling technique took into account certain parties who were considered to meet the criteria, knew, and understood Agen46. The results of this study indicate the role of Agen46 as a provider ofbranchless banking services for financial inclusion. The existence of agen46 is very beneficial for the people of Banjarnegara to meet their financial service needs